2023
DOI: 10.29333/ejmste/13086
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of motivation in STEM education: A systematic review

Abstract: Motivation is an essential factor influencing learners’ active participation in STEM subjects and their decision to study STEM fields. This study aimed to determine the current state of research on motivation and STEM and systematically review the current research in the literature. The study examined 78 articles published in journals indexed in the SCOPUS database. Two researchers collected and analyzed the data using the content analysis method. The results showed that the first research on motivation and ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Students, particularly those with LD, often have negative attitudes toward science, math, and other STEM disciplines due to many factors (e.g., lack of confidence, unpleasant prior experiences, and lack of instructional activities that stimulate students’ motivation and interest), which have been shown to be predictive of academic performance in STEM (Bayanova et al, 2023; Ng et al, 2016; Reynolds & Walberg, 1992; Singh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Students, particularly those with LD, often have negative attitudes toward science, math, and other STEM disciplines due to many factors (e.g., lack of confidence, unpleasant prior experiences, and lack of instructional activities that stimulate students’ motivation and interest), which have been shown to be predictive of academic performance in STEM (Bayanova et al, 2023; Ng et al, 2016; Reynolds & Walberg, 1992; Singh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies on mathematics have shown that the teacher's level of math anxiety influences the achievement of the girls in their classes, as well as the girls' formation of self-efficacy and self-concept in mathematics (Beilock et al, 2010). Teachers, of course, may also have a positive influence on their students and promote positive attitudes, high degrees of motivation, and a sense of self-efficacy and self-concept (Bayanova et al, 2023). Teachers' attitudes, beliefs, and feelings are also related to their teaching style and instructional strategies, e.g., the degree to which they include challenging tasks in mathematics instruction (Thompson et al, 2022).…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Practicum activities are rarely carried out in schools because of the lack of preparation of the materials needed. Motivation plays a crucial role in driving students to actively engage in STEM subjects and pursue careers in STEM fields (Bayanova et al, 2022). The implementation of STEM student worksheets in chemistry learning has a positive effect on students' motivation to learn science.…”
Section: Science Learning Motivationmentioning
confidence: 99%